Legend of the seeker. The complete 2nd and final season [videorecording (DVD)] - Horner, Craig, 1983-; Regan, Bridget, 1982-; Spence, Bruce; Parker, Craig, 1970-; Goodkind, Terry (ABC Studios, 2010)
The veil separating the world of the living from the underworld unleashes the most powerful forces the world has ever known. Only the mythical Stone of Tears can seal the cracks forming across the globe and only the Seeker, with the help of Kahlan and a fiery Mord'Sith named Cara, can find the stone and close the rift once and for all.